A Corporate Governance Dynamics and Financial Performance: Analysis of Listed Commercial Banks in the Ghanaian Context" - OWUSU, CALEB KWASI; Garr, David Kwashie (International Journal of Business, Management and Economics, 2024)
This study aims to determine the effect of corporate governance on the financial performance of 14 listed commercial banks in Ghana. The research employs a panel data set from 2008 to 2020 to examine how board size, ownership structure, board independence, capital adequacy ratio, audit committee effectiveness, board gender diversity, and overall corporate governance score affect ROA and ROE for banks. These relationships are analyzed using Ordinary Least Squares (OLS) regression within the framework of panel data analysis. Results indicate that ROA is positively related to board size, board independence, audit committee, and Board gender diversity. Also, ROE is positively influenced by companies’ ownership structure, capital adequacy ratio, audit committee effectiveness, and overall corporate employment governance rating. However, there is a significant negative correlation between ROE and women’s representation or board gender diversity. Also, another key finding is that both Return on Assets (ROA) and Return on Equity (ROE) are significantly affected by debt and debt-to-equity ratios. This indicates that banks borrowing more have reduced profitability, underlining the need for a well-managed capital structure and no over-reliance on loans. This study contributes to the understanding of the relationship between corporate governance and performance in the banking sector of Ghana, emphasizing that high-quality governance systems can improve and enhance financial performance. The insight gained from this analysis shows that Banks should aim towards good corporate governance practices such as; maintaining proper board size, promoting greater board independence, ensuring efficient audit procedures, and encouraging more gender diversity to enhance profitability. The outcomes also emphasized a well-built base of capital and concentrated ownership, enabling better financial results.The outcomes of this research are useful to Ghanaian policymakers, regulators, and bank executives who view the need for strong corporate governance environments to buttress the stability and growth of the banking sector.